1985
DOI: 10.1080/00288233.1985.10426999
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of concentrations of minerals and nitrogen in wheat grain, and their relationship with baking quality and grain weight

Abstract: The relationship between the mineral composition of grain and its baking quality was examined in 35 samples of wheat. Positive relationships were found between bake score and the nitrogen (N) and sulphur concentrations in the grain, and negative relationships with potassium (K) and molybdenum. Phosphorus and magnesium also gave significant, though weak, negative relationships. These individual nutrient relationships were unaffected by other elements, except for a significant N X K interaction. Bake score was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
3

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
4
0
3
Order By: Relevance
“…Some basic informations about mineral element concentrations are gathered in Table 3. The concentrations analysed agree well to already published data (DOUGLAS andDYSON 1985, GEISLER 1983). However in contrast to DOUGLAS and DYSON (1985) there was no significant correlation between phosphorous and potassium concentrations and baking quality parameters ( Table 2).…”
Section: Resultssupporting
confidence: 90%
“…Some basic informations about mineral element concentrations are gathered in Table 3. The concentrations analysed agree well to already published data (DOUGLAS andDYSON 1985, GEISLER 1983). However in contrast to DOUGLAS and DYSON (1985) there was no significant correlation between phosphorous and potassium concentrations and baking quality parameters ( Table 2).…”
Section: Resultssupporting
confidence: 90%
“…Bequette et al (1963) reported that the concentration of calcium in the water-soluble fraction and starch of wheat flour was positively correlated with bread loaf volume. Douglas and Tyson (1985) reported a positive relationship between bake score and the nitrogen and sulfur concentration in wheat grain, and a negative correlation between bake score and potassium and molybdenum concentration.Wheat that is bred to be naturally rich in micronutrients may be a complementary, inexpensive, and sustainable means of preventing mineral deficiency in human diets. The nutritional significance of minerals is well known and research is underway to develop nutritionally enhanced wheat (high in vitamins and minerals), but ash content has rarely been considered for its effects on the functionality of wheat flour.…”
mentioning
confidence: 95%
“…Bequette et al (1963) reported that the concentration of calcium in the water-soluble fraction and starch of wheat flour was positively correlated with bread loaf volume. Douglas and Tyson (1985) reported a positive relationship between bake score and the nitrogen and sulfur concentration in wheat grain, and a negative correlation between bake score and potassium and molybdenum concentration.…”
mentioning
confidence: 95%
“…Conversely V763-17, V763-252, and V763-2332 had higher grain nitrogen levels and flour protein than the standards but did not have better baking scores. Other unmeasured factors such as lipids (De Man & Dondeyne 1985) or other elements (Douglas & Dyson 1985) may be involved. Within these three lines, there was the same trend as the controls for better baking quality at higher levels of applied nitrogen.…”
Section: Resultsmentioning
confidence: 99%